种二氧化钌基复合纳米材料及其制备方法 (2018)
种二氧化钌基复合纳米材料及其制备方法。所述制备方法具体包括：将碳基体分散于水中，然后加入钌源和氧化性金属源，调节溶液pH值，搅拌吸附后，油浴反应，然后离心，洗涤，惰性气氛中煅烧即得所述复合纳米材料。该方法操作工艺简单、产率高、成本低、无污染，制得的二氧化钌/金属纳米颗粒/碳复合纳米材料活性成分尺寸细小，比表面积大，分散均。本发明二氧化钌为水合二氧化钌，是种良好的可逆充放电活性物质，金纳米颗粒易于吸附质子和传递电子，改善了二氧化钌/金属纳米颗粒/碳复合材料的电化学性能，用本发明制备的二氧化钌/金属纳米颗粒/碳复合材料作为超级电容器电极材料，有着优异的电化学性能。 The invention discloses ruthenium dioxide-based composite nano-material and a preparation method thereof. The preparation method includes that dispersing carbon matrix in water, adding ruthenium source and oxidized metal source, regulating the pH value of the solution, after stirring to adsorb, performing oil bath reaction, centrifuging, washing, and roasting in an inert atmosphere to obtain the composite nano-material. The preparation method is easy to operate, high in yield, low in cost and environmental friendly, and the prepared ruthenium dioxide/metal nano-particle/carbon composite nano-material is featured with small active ingredient size, large specific surface area and uniform dispersion. The ruthenium dioxide is hydrous